Informal learning in local farming practices by rural women in the Lake Chilwa Basin, Malawi: towards coping and adaptation to climate variability and climate change - Mphepo, Gibson Yadunda (Rhodes University, Faculty of Education, Department of Education, 2020)
Evidence reveals that informal learning is a neglected research area, globally and nationally. Informal learning, like formal and non-formal learning, is context specific. In the case of my study, the context was in local maize cultivation and the associated local farming practices which are also neglected. Research has shown that rural women in Malawi are significant change agents in socio-economic sectors, yet they are heavily affected by inequality. For example, extreme weather events of droughts and floods in the Lake Chilwa Basin, disproportionately affect more women than men because of their traditional gendered roles such as home care. The complexity of the dualistic nature of being change agents and victims of injustices at the same time offers a catalytic opportunity for potentially transformative social learning for transformative adaptation. Against this backdrop, I conducted a study to investigate and expand informal learning processes to contribute to building the resilience of women and other community members in Domasi and Nsanama Extension Planning Areas (EPA) within the Lake Chilwa Basin. Specifically, the study answered the following question: "How do drought and inter-seasonal dry spells influence informal learning processes to enable transformation adaptation among rural women cultivating maize in the Lake Chilwa Basin, Malawi?" To address the question, the first stage was to review local farming practices and the associated informal learning processes in Malawi. I then used third generation Cultural Historical Activity Theory (CHAT) as an overarching theoretical framework to guide the subsequent research processes which were split into three main phases: mirror data collection for expansive learning, formative change laboratory workshops, and data analysis and reflection. CHAT is a theoretical framework that helps us comprehend and analyze the relationship between the human mind (i.e. what people think and feel) and activity (what people do). It is a formative and activist learning theory that posits learning as occurring through collective activities to meet or change a common object (Mukute and Lotz-Sisitka, 2012, p. 345). For Koszalka and Wu, 2001(p. 493), within a CHAT framework, knowledge is socially constructed by individual learners, building on existing historical experiences, within the learners' context. To construct this knowledge, learners use technology or mediating tools, as Vygotsky (1978) calls them. To collect mirror data, I conducted focus group discussions, observation studies, and document analysis. I also conducted key informant interviews with selected extension workers responsible for the two case study sites. The hub of my research constituted change laboratory workshops to expand learning through four of the seven expansive learning actions, namely questioning, analysis, modeling and testing the model. One of the essential procedures I relied on to expand learning during these change laboratory workshops was identification and analysis of contradictions that were mirrored back to women. The use of contradictions as fertile ground for learning is premised on Engstrom's arguments that contradictions form a catalyst for learning. Data were analysed using two approaches: layered and power relations. A layered analysis is a step-by-step process of understanding a situation from the lower to a higher level (mature stage). For my research, this meant understanding sequential learning from questioning (session 1 "“ lower level) to testing the model (session 8 "“ higher level). The second data analysis approach, power relations, relates to the Women Empowerment in Agriculture Index (WEAI), a measure of the degree of women empowerment, their agency and inclusion in farming (Ruth et al., 2013, p. 3). I used this type of power analysis tool because my research was agriculture based. Both data analysis approaches relied on N-vivo which is a form of computer-based qualitative data management software. The software was ideal for my study which was also mostly qualitative. During phase 1 of data collection, I identified five local farming practices associated with local maize cultivation, a focus of my study. These practices were slash and burn (mphanje); traditional insect pest control measures; soil fertility enhancement techniques through kuojeka (crop residue incorporation) and livestock manure; traditional weather forecasts; and multiple cropping (mixed and sequential cropping). Among these, the most preferred by the women I interacted with were kuojeka, livestock manure and mixed cropping. I discovered that these local farming practices are informally learned mainly through word of mouth, observation, trials, women-dominated social networks and drama. I also discovered that some of these informal learning pathways are catalyzed by drought and dry spells. For example, during the 1949 and 2002 drought periods, women reported that they had learned new types of coping strategies such as the use of sawdust and banana root flour in place of maize flour to prepare nsima, a staple food in Malawi. During phase 2, change laboratory workshops, I identified 19 contradictions associated with local farming practices, most of which were related to the Government of Malawi bias towards modern farming practices such as hybrids. Other contradictions were related to traditional structures and norms and religion and traditional beliefs. Solutions were suggested for each of the contradictions. Some of these solutions were tested for their workability. These included setting up diversity blocks (demonstration plots) for local maize cultivation under irrigation and engagement of the youth through WhatsApp groups for the first time at the study sites. The results of the tests show that there is potential to transform local farming practices at the study sites and build social resilience against drought and dry spells. For example, from a local maize demonstration plot in Nsanama Extension Planning Area (EPA), farmers learned that kafula local maize is fast maturing and therefore cushions them against hunger as they wait for the main harvest in later months. Eighty-eight households shared local maize seed harvested from the demonstration gardens for upscaling. The Head of Nsanama EPA had also set up another demonstration garden in 2018-2019 growing season consisting of kafula at Nsanama EPA Headquarters for further informal learning purposes. This research has contributed new knowledge to the existing knowledge base about local farming practices and informal learning. These contributions are in the form of methods I used as well as results obtained. Among the key highlights of my contribution to the knowledge base is the development of scenarios as double stimulation tools for the emerging local farming activity system which emanates from the new model solutions resulting from change laboratory workshops. To the best of my knowledge, this was the first time rural communities were engaged in scenario development in Malawi. The first scenarios of this type were developed in 2010 for the Malawi State of Environment and Outlook Report and the process involved middle to senior managers of various institutions in Malawi. Through historical analysis, my research identified local crops that existed in the past but which are currently non-existent or rare. My study also identified unique local farming practices that even puzzled professionals, including the use of ripe banana peels of makumbuka and sukari to eradicate nansongole grass and native bamboos respectively. Both plant species are considered a nuisance in that they colonize land for cultivation. A breakthrough for radical transformation of local farming practices via informal learning requires development and review of relevant policies in Malawi. Such a process requires evidence. This research has provided background information for this process. For those policies already developed, this research has provided information that can help guide implementation of the generalized list of activities outlined in implementation plans of the respective policies.
Keywords: Women -- Non-formal education - Malawi; Non-formal education -- Malawi; Women -- Malawi -- Social conditions; Crops and climate -- Malawi; Agricultural extension work -- Government policy -- Malawi; Environmental education -- Malawi